Burden or Legacy : From the Chinese Cultural Revolution to Contemporary Art - Jiang, Jiehong (Book collections on Project MUSE., 2007)
This book consists of six papers by the scholars and the artists in China and in the UK, discussing contemporary Chinese art with the influence from the Chinese Cultural Revolution.